Dementia Scale Score Classification Based on Daily Activities Using Multiple Sensors - Akira Minamisawa; Shogo Okada; Ken Inoue; Mami Noguchi (IEEE Access)
Early detection of age-related disease symptoms in older people by the use of daily activity data is one of the central challenges of home sensor systems. This paper focuses on dementia scale classification from daily activity data collected using sensors that can be deployed in actual residential environments. Activity data collected by four sensors (a door sensor, human motion sensor, location sensor, and sleep sensor) were obtained by recording 56 older adults living in common residences. We analyzed the effects of different types of sensor data, such as time spent in an individual room according to human motion sensors, location in a facility, and sleep patterns, on dementia detection. We then developed a feature extraction method related to daily activity patterns based on a clustering algorithm and analyzed its effectiveness. In the experimental evaluation, we trained binary classification models to classify dementia scale scores based on the Mini-Mental State Examination (MMSE) from these datasets. The experimental results show that a maximum accuracy of 0.871 was obtained with a linear support vector machine (SVM) model by fusing the door, location, and sleep features and by clustering activity patterns using the X-means algorithm.